SINTESIS FISIKOKIMIA DARI KARBON AKTIF BERBASIS BIOMASSA SABUT NIPAH (Nypa fruticans) UNTUK PERFORMANSI KINERJA SUPERKAPASITOR - Irma Apriyani; Rakhmawati Farma; Awitdrus Awitdrus; Aria Yunita (Komunikasi Fisika Indonesia, 2023)
Biomass-based activated carbon materials provide a new approach for the development of high-performance electrode materials for supercapacitor cells. In addition, the carbon materials are low cost and sustainable for large-scale production of electrode materials. In this study, carbon electrodes made from nipa palm (Nypa fruticans) coir were synthesized physicochemically. The pore size distribution of the carbon electrodes can be adjusted with the increased CO2 activation temperature (700°C, 800°C, and 900°C). The results showed that the SN-800 carbon electrode had the lowest density shrinkage and showed excellent electrochemical performance. The highest specific capacitance was obtained at 247 F/g at a current density of 1 A/g in a symmetrical two-electrode system. This work provides an efficient strategy for the preparation of high performance carbon electrodes based on nipa coir biomass.